Dampak Profitabilitas Terhadap Harga Saham Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013 - 2017 (Studi Pada Perusahaan Makanan dan Minuman) - Nur Ainiyah; Toto Heru Dwihandoko (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
The market where the issuers and investors meet is called the capital market. One of the products sold in the capital market is stock. High and low price of a stock is influenced by the profitability of one company. The purpose of this study was to determine the effect of the effect of profitability proxied by ROE, EPS and NPM on stock prices in food and beverage companies in 2013-2017. This type of research uses quantitative research. The object of research in the food and beverage companies in the period 2013-2017 and a sample of 12 companies. The type of research data used is secondary data, namely financial statement data obtained from the Indonesia Stock Exchange (IDX) and research data analysis method, namely multiple linear regression. The results showed that the ROE variable partially had no effect on stock prices with a significance value of 0.830. And the EPS NPM variable influences the stock price with a significance value of 0.004 and 0.00. And simultaneously the variable ROE, EPS and NPM affect the stock price with a significance value of 0,000.